Efficient synthesis of 1,5-benzodiazepines catalyzed by bismuth nitrate - Bhattacharya, Asish K.; Dange, Santoshkumar S.; Polanki, Innaiah K.; Chand, Hemender R. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2014)
An efficient method has been developed for the synthesis of biologically active 1,5-benzodiazepines in one-pot by reacting o-phenylenediamine and ketones catalyzed by bismuth nitrate pentahydrate at room temperature or under microwave irradiation.
Keywords: 1; 5-benzodiazepines; bismuth nitrate pentahydrate; o-Phenylenediamine; synthetic methods

Design, synthesis, and identification of silicon incorporated oxazolidinone antibiotics with improved brain exposure - Seetharamsingh, B.; Ramesh, Remya; Dange, Santoshkumar S.; Khairnar, Pankaj V.; Singhal, Smita; Upadhyay, Dilip; Veeraraghavan, Sridhar; Viswanadha, Srikant; Vakkalanka, Swaroop; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Therapeutic options for brain infections caused by pathogens with a reduced sensitivity to drugs are limited. Recent reports on the potential use of linezolid in treating brain infections prompted us to design novel compounds around this scaffold. Herein, we describe the design and synthesis of various oxazolidinone antibiotics with the incorporation of silicon. Our findings in preclinical species suggest that silicon incorporation is highly useful in improving brain exposures. Interestingly, three compounds from this series demonstrated up to a 30-fold higher brain/plasma ratio when compared to linezolid thereby indicating their therapeutic potential in brain associated disorders.
Keywords: Antibacterial; brain exposure; linezolid; oxazolidinone; sila analogue

Comprehensive study on solomonamides: total synthesis, stereochemical revision, and SAR studies toward identification of simplified lead - Jachak, Gorakhnath R.; Kashinath, K.; Vasudevan, N.; Athawale, Paresh R.; Choudhury, Rahul; Dange, Santoshkumar S.; Agarwal, Heena; Barthwal, Manoj Kumar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2023)
Solomonamides, a pair of macrocyclic peptide natural products originating from marine sources, have garnered significant attention within the synthetic community owing to their marked anti-inflammatory efficacy and intricate molecular architectures. In this paper, we present a very detailed investigation into solomonamides, including the challenges associated with the total synthesis, the evolution of our synthetic strategies, structural reassignment, synthesis of all possible stereoisomeric macrocycles, biological assessment, structure-activity relationship (SAR) studies, etc. Within the ambit of this total synthesis, diverse strategies for macrocyclization were rigorously explored, encompassing the Friedel-Crafts acylation, cyclization involving the aniline NH2 moiety, macrolactamization utilizing Gly-NH2, and Heck macrocyclization methodologies. In addition, an array of intriguing chemical transformations were devised, including but not limited to photo-Fries rearrangement, Wacker oxidation, ligand-free Heck macrocyclization, oxidative cleavage of indole, synthesis of contiguous stereocenters via substrate/reagent-controlled protocols, and simultaneous making and breaking of olefinic moieties. The findings of this investigation revealed a structurally simplified lead compound. Remarkably, the lead compound, while possessing structural simplification in comparison to the intricate solomonamide counterparts, demonstrates equipotent in vivo anti-inflammatory efficacy.